2021
DOI: 10.3390/ani11071984
|View full text |Cite
|
Sign up to set email alerts
|

Absence of SARS-CoV-2 Antibodies in Natural Environment Exposure in Sheep in Close Contact with Humans

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the zoonotic causative agent of coronavirus disease 2019 (COVID-19) that has caused a pandemic situation with millions of infected humans worldwide. Among domestic animals, there have been limited studies regarding the transmissibility and exposure to the infection in natural conditions. Some animals are exposed and/or susceptible to SARS-CoV-2 infection, such as cats, ferrets and dogs. By contrast, there is no information about the susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Moreover, novel SARS-CoV-2 variants or recombinant strains with widely circulating swine and bovine coronaviruses could potentially change this situation. An in vitro study indicated that SARS-CoV-2 can replicate in ex vivo respiratory tissue from sheep [ 233 ], although a recent study suggests resistance in sheep to natural SARS-CoV-2 infection [ 234 ]. Experimental studies of SARS-CoV-2 infection in sheep—and other farmed species, namely goats, equids, and camelids—should be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, novel SARS-CoV-2 variants or recombinant strains with widely circulating swine and bovine coronaviruses could potentially change this situation. An in vitro study indicated that SARS-CoV-2 can replicate in ex vivo respiratory tissue from sheep [ 233 ], although a recent study suggests resistance in sheep to natural SARS-CoV-2 infection [ 234 ]. Experimental studies of SARS-CoV-2 infection in sheep—and other farmed species, namely goats, equids, and camelids—should be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA sequence encoding amino acid residues 319-541 (RVQPTESIVRFPNITNLCPFGEVFNATRFASVYAWNRKRISNCVADYSVLYNSASFSTFKCYGVSPTKLNDLCFTNVYADSFVIRGDEVRQIAPGQTGKIADYNYKLPDDFTGCVIAWNSNNLDSKVGGNYNYLYRLFRKSNLKPFERDISTEIYQAGSTPCNGVEGFNCYFPLQSYGFQPTNGVGYQPYRVVVLSFELLHAPATVCGPKKSTNLVKNKCVNF) of the RBD was codon optimized and synthesized by Gen-Script (Piscataway, NJ, USA) for expression in HEK293 cells, as described previously [ 11 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…An in-house indirect ELISA for the detection of IgG specific to RBD of Spike protein was established with some modifications [ 11 , 31 , 32 ]. As a positive control, each plate included two serum samples, including a human patient diagnosed with COVID-19, confirmed by a molecular test and a commercial quantitative ELISA, and two serum samples from a seropositive cat [ 31 ] and a seropositive ferret to SARS-CoV-2 [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…To date, no natural infection in sheep and goats has been observed. Indeed, little information is available for goats and a serological study was performed in Spain in sheep but without revealing anti-SARS-CoV-2 antibodies (Villanueva-Saz et al, 2021 ). Bosco-Lauth and colleagues ( 2021 ) evaluated the susceptibility of livestock to SARS-CoV-2 by experimental infections.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, challenged small ruminants show anti-SARS-CoV-2 detectable antibodies but for a short time after infection and low titers of neutralizing antibodies (Gaudreault et al 2021 ; Bosco-Lauth et al 2021 ). Altogether, these observations have led to the conclusion that sheep and goats have low susceptibility to SARS-CoV-2 and natural infection is unlikely to occur (Gaudreault et al 2021 ; Villanueva-Saz et al, 2021 ; Bosco-Lauth et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%